2005
DOI: 10.1158/0008-5472.can-05-1394
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor–Induced p42/44 Mitogen-Activated Protein Kinase Activation and Cellular Growth Is Mediated by Reactive Oxygen Species in the Absence of TSC2/Tuberin

Abstract: Tuberous sclerosis complex (TSC) is a genetic disorder caused by inactivating mutations in the TSC1 or TSC2 genes, which encode hamartin and tuberin, respectively. TSC is characterized by multiple tumors of the brain, kidney, heart, and skin. Tuberin and hamartin inhibit signaling by the mammalian target of rapamycin (mTOR) but there are limited studies of their involvement in other pathways controlling cell growth. Using ELT-3 cells, which are Eker rat-derived smooth muscle cells, we show that ELT-3 cells exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
5
18
0
Order By: Relevance
“…AMPK is in turn regulated at least in part through the LKB1 tumor suppressor gene involved in Peutz Jaegher's Syndrome, another cancer predisposing hamartoma syndrome (10). Like ATM-deficient cells, TSC2-null cells exhibit defects in redox homeostasis (11)(12)(13).…”
mentioning
confidence: 99%
“…AMPK is in turn regulated at least in part through the LKB1 tumor suppressor gene involved in Peutz Jaegher's Syndrome, another cancer predisposing hamartoma syndrome (10). Like ATM-deficient cells, TSC2-null cells exhibit defects in redox homeostasis (11)(12)(13).…”
mentioning
confidence: 99%
“…Moreover, increased sensitivity of Tsc2 À/À cells relative to Tsc2 We have previously shown that the growth advantage conferred by the loss of tuberin in ELT-3 cells is most apparent under conditions of serum withdrawal (30) and that Tsc2 À/À ELT-3 cell growth is also estrogen responsive (24). Figure 1B shows that …”
Section: Atorvastatin Inhibits the Growth Of Tsc2mentioning
confidence: 88%
“…The response of TSC2 À/À MEFs to peroxide is somewhat puzzling, as basal ROS levels are significantly higher in TSC2 À/À cells, as a result of increased mitochondrial function (Finlay et al, 2005). Moreover, peroxide or arsenite treatment of JB6 cells (a mouse epidermal cell type) has been shown to lead to an increase in S6K and 4EBP1 activation (Bae et al, 1999;Huang et al, 2002;Jung et al, 2003).…”
Section: Rosmentioning
confidence: 99%